Canada : Selected Issues. (IMF Staff Country Reports; Country Report, 2000)
The issue of productivity growth in Canada has received considerable attention reflecting its marked slowdown since the early 1970s and concerns about its implications for Canadian competitiveness. To better understand productivity developments in Canada, it is useful to decompose total factor productivity (TFP) into investment-specific productivity change (ISP) and technologically neutral productivity change (TNP). The gap in manufacturing productivity growth between Canada and the United States originates mostly in the strong performance of specific industries, such as electrical products and commercial and industrial machinery.